Persistent Poverty in Rural China: Where, Why, and How to Escape? - Thomas Glauben; Thomas Herzfeld; Scott Rozelle; Xiaobing Wang (World Development, 2012)
Using rural household panel data from three Chinese provinces, this paper identifies determinants of long-term poverty and tests the duration dependence on the probability to leave poverty. Special emphasis is given to the selection of the poverty line and inter-regional differences across provinces. Results suggest that the majority of population seems to be only temporary poor. However, the probability to leave poverty for those who were poor is differently affected by poverty duration across provinces ranging from no duration dependence in Zhejiang to highly significant duration dependence in Yunnan. The number of nonworking family members, education, and several village characteristics seem to be the most important covariates.
Keywords: 330; poverty; Asia; China; rural population; hazard analysis; dynamics